Drinking Risk Level Reductions Associated with Improvements in Physical Health and Quality of Life Among Individuals with Alcohol Use Disorder. (5th November 2018) - Witkiewitz, Katie; Kranzler, Henry R.; Hallgren, Kevin A.; O'Malley, Stephanie S.; Falk, Daniel E.; Litten, Raye Z.; Hasin, Deborah S.; Mann, Karl F.; Anton, Raymond F.
Abstract : Background: Abstinence and no heavy drinking days are currently the only Food and Drug Administration–approved end points in clinical trials for alcohol use disorder (AUD). Many individuals who fail to meet these criteria may substantially reduce their drinking during treatment, and most individuals with AUD prefer drinking reduction goals. One‐ and two‐level reductions in World Health Organization (WHO) drinking risk levels have been proposed as alternative end points that reflect reduced drinking and are associated with reductions in drinking consequences, improvements in mental health, and reduced risk of developing alcohol dependence. The current study examined the association between WHO drinking risk level reductions and improvements in physical health and quality of life in a sample of individuals with alcohol dependence. Methods: Secondary data analysis of individuals with alcohol dependence ( n  = 1, 142) enrolled in the longitudinal, prospective COMBINE study, a multi site randomized placebo‐controlled clinical trial, examining the association between reductions in WHO drinking risk levels and change in blood pressure, liver enzyme levels, and self‐reported quality of life following treatment for alcohol dependence. Results: One‐ and two‐level reductions in WHO drinking risk level during treatment were associated with significant reductions in systolic blood pressure ( p  <   0.001), improvements in liver enzyme levels (all p  <   0.01), and significantly better quality of life ( p  <   0.001). Conclusions: One‐ and two‐level reductions in WHO drinking risk levels predicted significant improvements in markers of physical health and quality of life, suggesting that the WHO drinking risk level reduction could be a meaningful surrogate marker of improvements in how a person "feels and functions" following treatment for alcohol dependence. The WHO drinking risk levels could be useful in medical practice for identifying drinking reduction targets that correspond with clinically significant improvements in health and quality of life. Abstract : At least 1‐ and 2‐level reductions in the World Health Organization (WHO) drinking risk levels by the end of treatment were associated with significant improvements at the end of treatment for physical health and quality of life outcomes. The WHO drinking risk level reductions capture considerable improvement in how patients feel and function in alcohol clinical trials.